(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
At food industry enterprises, it is possible to use only environmentally safe inhibitors, for example, of plant origin, for anti-corrosion protection of metal communications and equipment. The purpose of the scientific research was to obtain grape seed extract and to study its anti-corrosion effect on the stability of steels used for manufacturing equipment of food enterprises. According to the chromatographic study, the water-ethanol extract of grape seed powder contains terpene alcohols, aldehydes, phenolic acids, flavonoids, stilbenes, etc. The maximum value of the total content of polyphenols is observed in the extractant with the content of water and ethanol in a ratio of 50:50, which is equal to 42.3 mg/g in gallic acid equivalent per 1 g of dry powder. That is, the content of polyphenols is almost 4.5% of the mass of dry substances of the powder in the equivalent of gallic acid. Therefore, in the future, a 50% water-ethanol solution (1 mass part of dry powder / 10 mass parts of extractant) was used to obtain inhibitors. Gravimetric and electrochemical (polarization resistance indicator P5126) methods were used to evaluate the anti-corrosion properties of the extract. It was found that the optimal amount of grape seed extract in 0.1 M HCl solution for corrosion protection of steels is 30 g/l, the degree of protection is 93.6 - 97.3% depending on the type of steel. Thus, the water-alcohol extract of grape seed powder obtained by us is an effective means of protecting metals from corrosion. The presence of a significant amount of substances of a polyphenolic nature and terpenes in the extract ensures the formation of a passive protective layer on the surface of the steel.